Dental treatment of oral complications during radiation therapy of head and neck cancer - Daković Dragana; Ljušković Bešir; Jović Nebojša; Mileusnić Dušan (Serbian Medical Society - Dental Section, Belgrade, 2002)
Radiation therapy is often used as primary or adjuvant therapy for malignancy of the oropharyngeal region. Inflammatory changes of the oral mucosa resulting from the direct effect of radiation therapy, are defined as Radiation Mucositis (RM). As a consequence of irradiation, patients have xerostomia, pain, difficulty in chewing and swallowing, dental caries, oral microbial changes, chronic esophagitis, periodontitis, osteoradionecrosis. To eliminate or decrease discomfort in oral cavity, the use of various mouth rinses is recommended for compromised patients. These solutions should reduce pain, promote reepithelialization of soft tissue lesions, normalize the pH of oral fluids. They should be nontoxic, and to have acceptable taste. In the modern practice of head and neck oncology, dentists are essential members of the team. Their contribution is essential in improvement of the patients' quality of life.